High-grade left atrial pleomorphic sarcoma: case report and review (2017)
Primary pleomorphic sarcoma of the left atrium is a rare tumor. There is no actual evidence of the management of this pathological entity, so the main treatment is individualized, surgical management being the cornerstone of the treatment. We present a 78-year-old female who had a clinical picture of heart failure, documenting an atrial mass of the left atrium, with high-grade pleomorphic sarcoma revealed in histopathology. The tumor was surgical removed, with no clinical evidence of residual mass. The tumor recurred again within 3 years, to which the patient succumbed.